2013
DOI: 10.6061/clinics/2013(06)11
|View full text |Cite
|
Sign up to set email alerts
|

Oral health as a predictive factor for oral mucositis

Abstract: OBJECTIVES:Oral mucositis is a complication frequently associated with hematopoietic stem cell transplantation, decreasing a patient's quality of life and increasing the occurrence of opportunistic infections. The purpose of this study was to determine the incidence and severity of oral mucositis and to assess the correlation of this disease with the oral health of an individual at the time of hematopoietic stem cell transplantation.METHODS:Before transplantation, patients' oral health and inflammatory conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
2
16
0
3
Order By: Relevance
“…Several authors have investigated possible associations of oral health condition prior to transplantation with the incidence and severity of complications in the immediate post-transplant period. 2,[8][9][10][11][12][13][14][15][16][17] Among the oral diseases described in candidates for HSCT, periodontal diseases, mainly gingivitis and periodontitis, are the most frequent 18 and most often associated with sepsis. 3,19 The periodontal diseases present a wide heterogeneity in extent, severity, progress, and treatment response.…”
Section: Periodontal Status Of Candidates For Allogeneic Hematopoietimentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have investigated possible associations of oral health condition prior to transplantation with the incidence and severity of complications in the immediate post-transplant period. 2,[8][9][10][11][12][13][14][15][16][17] Among the oral diseases described in candidates for HSCT, periodontal diseases, mainly gingivitis and periodontitis, are the most frequent 18 and most often associated with sepsis. 3,19 The periodontal diseases present a wide heterogeneity in extent, severity, progress, and treatment response.…”
Section: Periodontal Status Of Candidates For Allogeneic Hematopoietimentioning
confidence: 99%
“…The mouth is a frequent site of local infections and an important port of entry for systemic infections in HSCT recipients. Several authors have investigated possible associations of oral health condition prior to transplantation with the incidence and severity of complications in the immediate post‐transplant period . Among the oral diseases described in candidates for HSCT, periodontal diseases, mainly gingivitis and periodontitis, are the most frequent and most often associated with sepsis …”
Section: Introductionmentioning
confidence: 99%
“…In this context, an interdisciplinary approach (with the participation of nurses, physicians, dentists, dental hygienists, dieticians, pharmacists, and others as relevant) will prevent the development of OM and/or treat the condition (da Silva Santos et al, 2011;McGuire et al, 2013) have reported a decrease the time elapsed of OM in patients with OM receiving oral care before haematopoetic stem cell transplantation (da Silva Santos et al, 2011). In another study, it has been observed that oral care can reduce the severity and incidence of OM (Coracin et al, 2013). On the other hand, some reports have shown that oral problems are not adequately addressed in cancer patients undergoing chemotherapy, that these problems are inadequately treated due to being ignored by both doctors and nurses, and that there is a lack of nursing interventions for cancer patients who have oral mucositis (Araújo et al, 2015;Daniel, Damato, & Johnson, 2004;Honnor & Law, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cursa com ulcerações dolorosas recobertas por exsudato fibrinoso (pseudomembrana) de coloração esbranquiçada ou opalescente. Além da importante sintomatologia, as ulcerações aumentam o risco de infecção local e sistêmica, comprometem a função oral e interferem no tratamento antineoplásico, podendo levar à sua interrupção, o que compromete a sobrevida do paciente [10][11] . Compreendendo as sequelas causadas ao paciente acometido pela mucosite, percebe-se a grande relevância de uma terapia adequada para prevenir a sua ocorrência ou acelerar a sua resolução, o que traz benefício clínico significativo, bem como redução de custos na área de saúde 12 …”
Section: Introductionunclassified